White Wings: A Yachting Romance, Volume III - Black, William, 1841-1898 (Salt Lake City, UT : Project Gutenberg, 2013)
"White Wings: A Yachting Romance, Volume III" by William Black is a novel written in the late 19th century. The story centers around a group of characters sailing on the yacht "White Dove," including the young artist Mary Avon, the Laird, the Doctor Angus Sutherland, and others as they navigate both the seas and their interpersonal relationships. As they enjoy their time yachting in beautiful yet wild Scottish landscapes, the story is filled with humor, romance, and reflections on life and duty. The opening of the novel introduces readers to a group of friends exploring an island while hunting for sea creatures, with a focus on Mary Avon and her artistic pursuits. Mary is seen interacting with the Laird, a cheerful and supportive figure, along with the cautious Doctor Sutherland, who is enamored with her. Their dynamic hints at underlying feelings and tensions, particularly concerning Sutherland's recent proposal to Mary, which she has declined. This sets the stage for emotional struggles and developments as the characters continue their journey on the yacht, signaling an exploration of themes such as love, aspiration, and the complexity of human relationships amidst the backdrop of nature's beauty. (This is an automatically generated summary.)
Release date is 2013-09-27
Produced by Al Haines
Keywords: Yachting -- Fiction